0
$\begingroup$

I am attempting to find the derivative of $\sqrt{3\cos^3 x}$.

Using the chain rule, I got:

$$\frac{1}{2} \sqrt{(3\cos x)^3} × 3(3\cos x)^2 × (-3\sin x).$$

Apparently this is where I went wrong, the correct answer stated that instead of the derivative of the inner function should have been $-\sin x$ instead of $-3\sin x$. To my understanding the derivative of $3\cos x$ is $-3\sin x$. Is my reasoning incorrect?

$\endgroup$
2
$\begingroup$

$$\begin{align*} \frac{\mathrm{d}}{\mathrm{d}x}\sqrt{3\cos^3x} &= \sqrt{3}\cdot\frac{\mathrm{d}}{\mathrm{d}x}\cos^\frac32x\\ &= \sqrt{3}\cdot\frac32\cos^{\frac32 - 1}x\cdot\frac{\mathrm{d}}{\mathrm{d}x}\cos x\\ &= \sqrt{3}\cdot\frac32\cos^\frac12x\cdot(-\sin x) \\ &= -\frac{3^\frac32}{2}\sin x\sqrt{\cos x} \end{align*}$$

$\endgroup$
0
$\begingroup$

You have to be more careful with negative exponents.

$$ d/dx (\sqrt{3\cos^3 x}) = d/dx (3\cos^3 x)^{1/2}= $$

$$ (1/2)(3\cos^3 x)^{-1/2}(9\cos^2 x )(-\sin x)=$$

$$(-3 \sqrt 3/2)(\cos ^{1/2}x)\sin x =$$

$$(-3 \sqrt 3/2)\sin x \sqrt {\cos x} $$

$\endgroup$
  • $\begingroup$ why is d(3cosx)/dx = -sinx? cosx is being multiplied by a constant, therefore by the constant rule, shouldnt it be -3cosx? $\endgroup$ – user543643 Mar 20 '18 at 5:36
  • $\begingroup$ You are correct. derivative of 3cos(x) is -3sin(x). When multiplied by other numbers you get the result that you see. The 9 in second row of my solution is the result of $3\times $3 $\endgroup$ – Mohammad Riazi-Kermani Mar 20 '18 at 7:19
0
$\begingroup$

For this kind of problems, logarithmic differentiation makes life much easier $$y=\sqrt{3\cos^3 (x)}\implies \log(y)=\log(\sqrt{3})+\frac 32 \log(\cos(x))$$ Differentiate both sides $$\frac{y'} y=-\frac 3 2 \frac{\sin(x)}{\cos(x)}$$ $$y'=y \times \frac{y'} y= ???$$ Simplify.

$\endgroup$
-1
$\begingroup$

Here is a correct implementation of chain rule

$\frac{d\sqrt{3cos^3(x)}}{dx} = \frac{1}{2\sqrt{3cos^3(x)}}*\frac{d( {3cos^3(x)})}{dx}$ = $\frac{1}{2\sqrt{3cos^3(x)}}*3*3*cos^2(x)*\frac{d({cos(x)})}{dx}$

$\qquad \qquad = \frac{1}{2\sqrt{3cos^3(x)}}*9*cos^2(x)*(-sin(x)) = -\frac{3^{\frac{3}{2}}}{2}*sin(x)*\sqrt{cos(x)}$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.